Adaptation strategies and adequacy of planning for learning in the context of COVID-19 and intersectionality - Pajares Cohaila, Aydee (2023)
The main objective of this study was to delve deeper into the everyday issues that emerged in the process of curricular diversification during the implementation of the distance education strategy "Aprendo en casa" in educational institutions in Tacna, within the context of the Covid-19 pandemic. To achieve this, a basic exploratory-descriptive research was conducted, adopting a qualitative approach, as the investigative action aimed at interpreting the data obtained through in-depth structured interviews conducted with administrators in the year 2021. The sample consisted of 12 administrators from public primary and secondary educational institutions, and the selection was based on convenience. The findings shed light on the intersectional nature of inequalities among students and the strategies that teachers designed to meet their needs.